Pengembangan Badan Usaha Milik Desa Melalui Peningkatan Kualitas Sumber Daya Manusia: Kualitas Sumber Daya Manusia; BUMDes; Strategi Pengembangan Usaha - Azhari Azhari; Moh . Mustofa; Erika Dwi Meisari; Erika Tri Setia Anggarista (Jurnal Ilmiah Ekonomi Global Masa Kini, 2023)
This research aims to determine the strategy for developing Village-Owned Enterprises (BUMDes) through improving the quality of human resources. In general, the role of BUMDes is very significant in improving community welfare. BUMDes plays a role as the main driver in developing local economic potential at the village level. This research method was carried out using a qualitative analysis approach and adding simple quantitative analysis. The data used in this research is primary data taken directly from key people who have been determined in this research so that it can provide representative decision results. The results of this research can be explained that improving the quality of human resources is the main component in the development of BUMDes in Bojonegoro Regency. Meanwhile, increasing human resources in developing BUMDes in Bojonegoro Regency can be done through increasing innovation followed by education, knowledge and experience. Thus improving the quality of human resources in the development of BUMDes in Bojonegoro Regency can prioritize increased innovation. The results of this research can provide empirical benefits as a basis for policies carried out to develop BUMDes which can be done by prioritizing increasing human resources as one of the most important aspects in efforts to develop BUMDes by increasing innovation in BUMDes management, education, knowledge and experience possessed by BUMDes actors. , This research has limitations, namely that the analysis used can only focus on the development of BUMDes in Bojonegoro Regency.  Keywords: Quality of Human Resources; BUMDes; Business Development Strategy